Pemenuhan Hak Anak Bawaan Narapidana Wanita yang Tinggal dan Masuk Pada Lingkungan Lembaga Pemasyarakatan - Putri, Tarisa Veronika; Subroto, Mitro (Universitas Ekasakti, 2023)
This study aims to determine the rights obtained by every child of female prisoners who live and enter the correctional environment. The research method used in this research is a qualitative research method that emphasizes the phenomenon and the meaning of the phenomenon which is then analyzed by the norms in the existing laws and regulations. The data source used is secondary data in the form of laws and regulations, policies, literature, previous research results, and other related documents. The results showed that there are already laws and policies that have regulated the fulfillment of the rights of children born to women prisoners both international and national regulations, although there are no guidelines related to the fulfillment of these rights, as well as the discovery of obstacles in the form of regulations, budgeting, human resources, facilities and infrastructure and cooperation in fulfilling the rights of children born to women prisoners so that it is hoped that the drafting of regulations to overcome this.